2001
DOI: 10.1177/106342660100900306
|View full text |Cite
|
Sign up to set email alerts
|

Placement Disruption in Treatment Foster Care

Abstract: Rates of placement disruption in traditional and treatment foster care are reviewed. Contextual factors, individual child and caregiver characteristics, and risk factors thought to influence rates of placement disruption are explored. A model for treatment foster care is described, and data are presented on disruption rates for this program. The results indicated that the likelihood of placement disruption is two times higher during the first 6 months (17.8%) compared to the second 6 months (9.2%) of treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
55
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(61 citation statements)
references
References 14 publications
1
55
0
5
Order By: Relevance
“…In a follow-up study of treatment foster care, it was also concluded that the treatment of adolescent girls was more often disrupted than the treatment of boys and younger girls (Smith, Stormshak, Chamberlain, & Bridges Whaley, 2001). It is possible that the circumstances in residential care are similar to the circumstances in treatment foster care.…”
Section: Summary and Discussionmentioning
confidence: 96%
“…In a follow-up study of treatment foster care, it was also concluded that the treatment of adolescent girls was more often disrupted than the treatment of boys and younger girls (Smith, Stormshak, Chamberlain, & Bridges Whaley, 2001). It is possible that the circumstances in residential care are similar to the circumstances in treatment foster care.…”
Section: Summary and Discussionmentioning
confidence: 96%
“…Chamberlain et al (2006) found that children placed with relatives were less likely to change placements than children placed with non-relatives. There is also evidence that placement disruptions are most likely to occur early rather than later in a placement (e.g., Smith, Stormshack, Chamberlain, & Bridges, 2001). Thus, it appears that placement with a relative and finding a placement that is conducive to early placement stability may help to prevent later placement disruptions.…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests that the following variables predict placement disruption: (a) youth characteristics, most notably emotional and behavioral problems; (b) number of prior placements; and (c) quality of relationship with foster and biological families (Smith et al 2001;Zinn et al 2006). A much smaller body of research suggests that community interventions such as those using a wraparound model can improve the placement outcomes of youth in the foster care system by increasing the breadth, flexibility, and coordination of service provision (e.g., Clark et al 1996).…”
mentioning
confidence: 99%